Peran kepemimpinan transformasional dalam meningkatkan employee engagement dan dampaknya pada kinerja pegawai - Afiani, Riska; Surachim, Ahim; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2019)
The objectives of this research are to determine whether how much influence transformational leadership has on employee engagement and its implications for the performance of employees of public sector organizations. The design of this study was a cross-sectional method and used descriptive and verification type research methods. Data for this study were collected using a saturated sample with a total sample of 40 people. Analysis of this research data using simple linear regression with SPSS 24.0 for Windows computer software program (Statistical Product for Service Solution). The results of this study indicate that transformational leadership in public sector organizations is quite effective, employee engagement is in the high category and employee performance is in the high category. The current study found that the impact of effective transformational leadership can increase employee engagement and vice versa, if transformational leadership is not effective then employee engagement will not increase. This also happens to employee performance, if employee engagement is low it will result in low employee performance and conversely if employee engagement is high then the performance of employees will also increase.